Calculations for molecular biology and biotechnology : a guide to mathematics in the laboratory - Stephenson, Frank H. (Academic Press/Elsevier, 2010)
A must have for all Biotechnology Students and technicians. It walks readers through the minefield of laboratory calculations, helping to prevent the types of errors which could mean the loss of weeks of work. Key Features: * Topics range from basic scientific notations to complex subjects like nucleic acid chemistry and recombinant DNA technology * Each chapter includes a brief explanation of the concept and covers necessary definitions, theory and rationale for each type of calculation * Recent applications of the procedures and computations in clinical, academic, industrial and basic research laboratories are cited throughout the text New to this Edition: * Updated and increased coverage of real time PCR and the mathematics used to measure gene expression * More sample problems in every chapter for readers to practice concepts